1988
DOI: 10.1177/074355488833008
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Timing of Transition to Sexual Intercourse for Black Adolescent Females

Abstract: During the past three decades, sexual intercourse has increased in preva lence and has gradually become an earlier experience for young adoles cent females. Despite the prevalence, results of previous research have appeared to be inconsistent and noncumulative. A life course perspective and a sub-sample of Black females between 15-19 years of age from the National Survey of Family Growth Cycle III survey were used to identify the relationship between significant life events and other influences on the timing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

1992
1992
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 15 publications
2
16
0
1
Order By: Relevance
“…For example, ethnic identity has been associated with positive behaviors including high academic achievement (Bernal et al 1995), resiliency (Belgrave et al 2000;Miller 1999), self-esteem (Allen et al 1997;LorenzoHernández and Ouellette 1998;Martinez and Dukes 1997;McMahon and Watts 2002;Phinney and Chavira 1995;Spencer 1988), and self-efficacy (Smith et al 1999). Similarly, a lack of ethnic identity has been related to a number of unhealthy and maladaptive behaviors including antisocial behaviors (Jagers and Mock 1993;Smith et al 1999), violence (Hill et al 1994), cigarette smoking (Parker et al 1998), other substance use and addiction (Bates et al 1997;Beadnell et al 2003;Brook et al 1998;Herd and Grube 1996;Scheier et al 1997;Wallace 1999), and risky sexual behavior (Beadnell et al 2003;Leigh et al 1998;ScottJones et al 1989).…”
Section: Introductionmentioning
confidence: 96%
“…For example, ethnic identity has been associated with positive behaviors including high academic achievement (Bernal et al 1995), resiliency (Belgrave et al 2000;Miller 1999), self-esteem (Allen et al 1997;LorenzoHernández and Ouellette 1998;Martinez and Dukes 1997;McMahon and Watts 2002;Phinney and Chavira 1995;Spencer 1988), and self-efficacy (Smith et al 1999). Similarly, a lack of ethnic identity has been related to a number of unhealthy and maladaptive behaviors including antisocial behaviors (Jagers and Mock 1993;Smith et al 1999), violence (Hill et al 1994), cigarette smoking (Parker et al 1998), other substance use and addiction (Bates et al 1997;Beadnell et al 2003;Brook et al 1998;Herd and Grube 1996;Scheier et al 1997;Wallace 1999), and risky sexual behavior (Beadnell et al 2003;Leigh et al 1998;ScottJones et al 1989).…”
Section: Introductionmentioning
confidence: 96%
“…Religiosity has been associated with sexual risk behavior, however the nature of the relationship remains unclear. For example, studies have found church attendance to be associated with less risky sexual attitudes (Belgrave, Van Oss Marin, & Chambers, 2000), delayed sexual activity (Brewster, Cooksey, Guilkey, & Rindfuss, 1998;Cooksey, Rindfuss, & Guilkey, 1996;Donahue & Benson, 1995;Ku et al, 1993), increased condom use with current partner (Cooper, Peirce, & Huselid, 1994), and fewer sexual partners (in adolescents 16-19 years in Bachanas et al, 2002;Leigh, Weddle, & Loewen, 1988;Steinman & Zimmerman, 2004). However, the findings in some of these studies have not been consistent (e.g., no association found for 12-15-year-olds in Bachanas et al, 2002; associations found for some outcomes but not others in Cooper et al, 1994) and other studies have observed no relationship at all (e.g., Reitman et al, 1996).…”
Section: Introductionmentioning
confidence: 97%
“…Stereotypes about the sexual behavior of different groups are common (Leigh, Weddle & Loewen, 1988;Padilla & O'Grady, 1987); but educational and healthrelated decisions need to be based on empirical data so as to allocate efforts and resources correctly. Since unwanted pregnancies and sexually transmitted diseases (STDs), including AIDS, are serious problems on our campuses, as well as in society overall, data on the sexual practices and contraceptive behavior of the four most numerous ethnic groups can be quite useful.…”
mentioning
confidence: 99%